The taxonomic impediment of unrecognised flight polymorphism in Notonectidae (Hemiptera:Heteroptera) - Young, Euan C. (Zootaxa, 2010)
Foundation revisions of four genera within the Notonectidae (Hemiptera: Heteroptera: Nepomorpha) were reviewed to determine how the existence of previously unrecognised polymorphism of the wings or flight musculature might have led to confusion in the description of species. Specimens of the flightless morph may appear very different from flight capable ones. They are generally less pigmented and may be both smaller and less robust. In species descriptions the flightless morph can usually be readily diagnosed through the reduced pigmentation of the mesoscutellum. Flight-muscle and wing polymorphisms were found to be common in these genera. In Notonecta only one of the possible flying or flightless morphs was described in 51 of 60 species (85%), in Anisops in 64 of 80 species (80%), in Buenoa 26 of 35 species (74%), and in Enithares 11 of 33 species (33%). A greater recognition of the existence of flight polymorphism in this family can lead to more robust species descriptions and selection of type specimens. Within the four genera considered here alternative morphs are yet to be described in many species.